New record of a benthic chaetognath from Nalabana Island, Chilka Lake, Orissa - Acharya, Smita; Bohidar, K; Kar, S K (Indian Journal of Fisheries, 2011)
A benthic chaetognath of the species Spadella cephaloptera is reported for the first time from Chilka Lake, India.